Come Out and Play: Public Space Recovery, Social Capital, and Citizen Security - Matías Braun; Francisco Gallego; Rodrigo R. Soares (Institute of Labor Economics (IZA), 2023)
This paper examines the effects of renovating deteriorated public spaces on local socioeconomic outcomes. We analyze the impacts of a randomized experiment implemented in 28 fragile neighborhoods of Santiago, Chile. Our findings indicate that the renovation of local squares led to increased use and maintenance of the public space, enhanced neighborhood engagement, and a stronger sense of ownership among residents, along with a reduction in leisure activities outside the neighborhood. Moreover, treated neighborhoods experienced improvements in public security perceptions both within the square and in the broader neighborhood area. We also observe positive effects on trust (among acquaintances) and participation in community organizations. By exploring heterogeneous treatment effects across neighborhoods, we do not find evidence supporting theories emphasizing the joint determination of public security and social capital. Instead, our results suggest that the effects are better explained by increased neighborhood use, particularly in areas that are densely populated and have a higher proportion of social housing.
Keywords: K42; O18; R53; 330; public space recovery; crime; social capital; urban infrastructure